Understanding Agile Innovation Management Adoption for SMEs - Paul Jones (IEEE Transactions on Engineering Management, 2022)
Research interest in agile innovation management (AIM) has increased due to its growing popularity. However, little is known about adaptability by small and medium enterprises (SMEs). This study examines the factors affecting intention to adopt AIM in SMEs. A conceptual framework is developed by combining internal and external environmental factors that influence adoption intention. Responses were received from 276 SMEs and analyzed using covariance-based structural equation modeling (SEM). The results confirmed that external environmental factors of mimetic isomorphism and normative isomorphism have a positive association with the intention to adopt AIM. Moreover, the internal environmental factors of top management championship, adhocracy culture, clan culture, and organizational readiness were confirmed to be positively associated with AIM adoption. This study provides one of the first empirical evidence of AIM for SMEs. In doing so, the study contributes both theoretically and practically toward understanding strategies that would enhance adoption by SMEs.